A Divergent Enantioselective Total Synthesis of Post‐Iboga Indole Alkaloids. (18th August 2020) - Zhou, Jie; Tan, Dong‐Xing; Han, Fu‐She
Abstract: Divergent enantioselective total syntheses of five naturally occurring post‐iboga indole alkaloids, dippinine B and C, 10, 11‐demethoxychippiine, 3‐ O ‐methyl‐10, 11‐demethoxychippiine, and 3‐hydroxy‐3, 4‐secocoronaridine, as well as the two analogues 11‐demethoxydippinine A and D, are presented for the first time. The enantioenriched aza[3.3.1]‐bridged cycle, a common core intermediate to the target molecules, was constructed through an asymmetric phase‐transfer‐catalyzed Michael/aldol cascade reaction. The challenging azepane ring fused around the indole ring and the [3.3.1]‐bridged cycle were installed through an intramolecular SN 2′‐type reaction. These cyclization strategies enabled rapid construction of the [6.5.6.6.7]‐pentacyclic core at an early stage. Highlights of the late‐stage synthetic steps include a Pd‐catalyzed Stille coupling and a highly stereoselective catalyst‐controlled hydrogenation to incorporate the side chain at C20 with both R and S configurations in the natural products. Abstract : Enantioselective total syntheses of post‐iboga indole alkaloids were achieved in a divergent manner. The construction of the [6.5.6.6.7]‐pentacyclic core included an asymmetric Michael/aldol cascade reaction for installing the aza[3.3.1]‐bridged cycle and an intramolecular SN 2′‐type reaction for assembling the azepane ring. The stereoselective incorporation of the side chain involved a Pd‐catalyzed Stille coupling and a catalyst‐controlled hydrogenation.